PELATIHAN PENCATATAN AKUNTANSI SEDERHANA BAGI GENERASI MUDA DALAM MENGELOLA USAHA KREATIF - Made Susilawati; Eko Cahyo Mayndarto; Riah Ukur Br Ginting; Zainuddin Zainuddin; Afrizal Afrizal (Nindikayla Institute, 2026)
This community service activity aims to improve the understanding and skills of young people in conducting simple accounting records to support more structured and sustainable creative business management in Oebobo District, Kupang City. The problems faced by partners are low accounting literacy, unfamiliarity with recording financial transactions, and the lack of use of financial reports in business decision-making. The activity implementation methods include socialization, training, direct practice, and mentoring in preparing simple financial reports that include recording incoming and outgoing cash, preparing profit and loss reports, and business evaluations. The results of the activity showed an increase in participants' understanding of the importance of financial records and their ability to prepare simple financial reports independently. In addition, participants became more confident in managing business finances and were able to separate personal and business finances. This activity is expected to encourage the sustainability of creative businesses of the younger generation and improve business performance and competitiveness at the local level.